Petroleum Subsidy Withdrawal, Fuel Price Hikes and the Nigerian Economy - Inegbedion, Henry Egbezien; Inegbedion, Emmanuel; Obadiaru, Eseosa; Asaleye, Abiola (International Journal of Energy Economics and Policy, 2020)
The study investigated petroleum subsidy withdrawal, fuel price hikes and the Nigerian Economy. The purpose of the study was to determine the extent to which the removals of petroleum subsidies stimulate hikes in fuel prices and increases in the prices of products of other sectors in the Nigerian economy. It employed input-output model to determine the value added per sector from the computed table of flow of goods. Subsequently, the impacts of reductions in petroleum subsidies (10%, 20%, 30%, 40% and 50%) on the prices of products from the other sectors were computed. Results showed that reduction in petroleum subsidies stimulate increases in prices of petroleum products and such increases trigger increases in transport fares; increases in transport fares subsequently lead to increases in prices of other products owing to the degree of interdependency among the various sectors. The need for policy makers to be mindful of the economic implications of subsidy removal was suggested, among others. Keywords: Petroleum subsidy; Petroleum subsidy removal; Fuel Price Hike JEL Classification: H25 DOI: https://doi.org/10.32479/ijeep.8307